Vitamin D deficiency in children with asthma - Ullerithody, Kasim Resivi; Iyer, Rajalakshmi Harihara; Subharaman, Kinattinkara Ramachandran (International Journal of Contemporary Pediatrics, 2020)
Background: Asthma is one of the most common chronic respiratory diseases worldwide. Its exact cause remains unknown. Vitamin D has been implicated as a critical regulator of immunity and found to be associated with several immune mediated diseases. Recently there has been increasing interest in the possible link between vitamin D and asthma. Hence, we planned this study to assess the existence of any correlation between asthma and vitamin D levels in India. Methods: Fifty consecutive cases of clinically diagnosed asthma attending asthma clinic and those admitted in IMCH Calicut, Kerala, India were included in the study and administered detailed questionnaire. Routine physical examination and investigation as per the protocol in asthma clinic were done. Blood was drawn for 25 hydroxy cholecalciferol and serum analyzed by Roche Elecsys chemiluminescence assay. Controls were selected only after all fifty cases were selected. Vitamin D levels were assayed in the same manner as in patients with asthma. Vitamin D levels were then analyzed with other parameters and variables. Statistical analysis was performed using SPSS software, version 16. Results: Prevalence of vitamin D deficiency is high in study population. The difference in vitamin D levels between cases and controls is significant. Conclusions: More studies need to be done to ascertain the relationship between asthma and vitamin D in developing countries like India.